Evaluation of the forest composition in browsed Scots pine plantations - Noyce, Carl (2022)
Since the early 2000s browsing damage to Scots pine (Pinus Sylvestris) in the Götaland region of Sweden has been consistently estimated to be 15% per year, peaking at around 25% between 2009-2016, the highest of any region in the country. The Swedish Forest Agency has set a goal of achieving pine damage levels below 5% on average in the long-term, even if higher levels can be accepted in an individual year. Damage levels are influenced by a range of factors e.g., Scots pine density, moose density, tree species composition and forest stand management decisions. Scots pine monocultures planted for production forestry purposes are at risk of being replaced by competing species when browsing damage from moose (Alces alces) occurs. The aim of this study was to evaluate if intentional Scots pine plantations can be a future pine forest, or if browsing damage may be too severe to reach the goals of the investment. Fieldwork was carried out in 22 young stands located in Götaland which were regenerated with the planting of Scots pine between 2016-2018, on sites managed by forest owner association Södra Skogsägarna – who have raised the issue of what will become of Scots pine plantations. In addition, forest owners were interviewed regarding their aim with the regenerations and what they think about the possibility to combine Scots pine plantations with the population of moose. Results from the fieldwork indicated that the average damage level of Scots pine across all 22 stands was 25% and that Scots pine faces strong competition from regenerating Norway spruce (Picea abies), birch (Betula spp.) and other broadleaved species. Scenario analyses employed to determine the future dominant tree in stands revealed that targeted thinning may be necessary of competing trees to ensure Scots pine plantations are realised in the future. Results from the forest owner questionnaire indicated that forest owners’ management decisions are affected by browsing damage to Scots pine and that additional guidance from forest owner associations ...